1995
DOI: 10.1074/jbc.270.15.8495
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of the G Protein γ Subunit of Cone Photoreceptors

Abstract: The phototransduction process in cones has been proposed to involve a G protein that couples the signal from light-activated visual pigment to the effector cyclic GMP phosphodiesterase. Previously, we have identified and purified a G beta gamma complex composed of a G beta 3 isoform and an immunochemically distinct G gamma subunit (G gamma 8) from bovine retinal cones (Fung, B. K.-K., Lieberman, B. S., and Lee, R. H. (1992) J. Biol. Chem. 267, 24782-24788; Lee, R. H., Lieberman, B.S., Yamane, H. K., Bok, D., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…In addition, a novel cone-specific G␥ subunit (G␥ 8 ) has been reported recently (35). Preliminary immunohistochemical analysis of mouse retinal sections with antiserum CT215 indicates that G␤ 5 immunoreactivity is present in the plexiform layers, similar to the reported distribution for bovine G␥ 7 .…”
Section: Discussionmentioning
confidence: 52%
“…In addition, a novel cone-specific G␥ subunit (G␥ 8 ) has been reported recently (35). Preliminary immunohistochemical analysis of mouse retinal sections with antiserum CT215 indicates that G␤ 5 immunoreactivity is present in the plexiform layers, similar to the reported distribution for bovine G␥ 7 .…”
Section: Discussionmentioning
confidence: 52%
“…Given its presence in rods, the phosphoinositide pathway is most likely present in cones as well, thus raising questions about the identities of the corresponding PLC enzyme and G ␣ protein in cones. One G protein ␤-subunit (G ␤3 ), but two ␥-subunits (G ␥2 and G ␥8 ), have recently been identified in cone outer segments (55)(56)(57). Biochemical analysis suggests that, functionally, G ␥8 is likely the cone homolog of rod G ␥1 and coupled to cone transducin (G ␣t2 ) (57).…”
Section: Discussionmentioning
confidence: 99%
“…One G protein ␤-subunit (G ␤3 ), but two ␥-subunits (G ␥2 and G ␥8 ), have recently been identified in cone outer segments (55)(56)(57). Biochemical analysis suggests that, functionally, G ␥8 is likely the cone homolog of rod G ␥1 and coupled to cone transducin (G ␣t2 ) (57). Perhaps, then, G ␥2 is coupled to the yet-to-be-identified G q member in cone outer segments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ␤␥ dimers containing ␥ subunits from subfamily I such as ␥ 1 or ␥ 11 (and probably ␥ 8 , although it has not been studied extensively) seem to have unique signaling properties in that they are unable to activate type II adenylyl cyclase or other important effectors, such as phosphatidylinositol-(4,5)-3-kinase (Kerchner et al, 2004). The distribution of ␥ 1 is restricted to retinal rods (Fung, 1983), and the original report of ␥ 8 (termed ␥ c ) suggested that it was restricted to cone cells (Ong et al, 1995). However, the ␥ 11 subunit is widely expressed , and it now seems that ␥ 8 is also widely expressed (Downes and Gautam, 1999).…”
Section: Interaction Of G Proteinmentioning
confidence: 99%